2016
DOI: 10.1093/nutrit/nuw005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary interventions in overweight and obese pregnant women: a systematic review of the content, delivery, and outcomes of randomized controlled trials

Abstract: This review reveals large methodological variability in dietary interventions to control gestational weight gain and improve clinical outcomes in overweight and obese pregnant women. This lack of consensus limits the ability to develop clinical guidelines and apply the evidence in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 80 publications
2
126
0
Order By: Relevance
“…Most of these intervention studies, however, have not been of adequate size to provide sufficient statistical power to address pregnancy outcomes. A review of the strategies used has shown a lack of conformity and infrequent attempts to measure the impact of the interventions on diet or physical activity [38]. In a review of 12 randomized controlled trials involving a total of 2,713 pregnant women of normal BMI, EarlyNutrition researchers found that pregnant women of normal BMI who received a dietary and lifestyle intervention were likely to experience less GWG (4 studies, 446 women; mean difference -1.25 kg; 95% CI -2.39 to -0.11), less often reached a GWG exceeding the U.S. Institute of Medicine (IOM) guidelines (4 studies, 446 women; risk ratio 0.66; 95% CI 0.53-0.83) and reduced the incidence of hypertension (2 studies; 243 women; risk ratio 0.34; 95% CI 0.13-0.91).…”
Section: Recommendations On Nutrition During Preconceptionmentioning
confidence: 99%
“…Most of these intervention studies, however, have not been of adequate size to provide sufficient statistical power to address pregnancy outcomes. A review of the strategies used has shown a lack of conformity and infrequent attempts to measure the impact of the interventions on diet or physical activity [38]. In a review of 12 randomized controlled trials involving a total of 2,713 pregnant women of normal BMI, EarlyNutrition researchers found that pregnant women of normal BMI who received a dietary and lifestyle intervention were likely to experience less GWG (4 studies, 446 women; mean difference -1.25 kg; 95% CI -2.39 to -0.11), less often reached a GWG exceeding the U.S. Institute of Medicine (IOM) guidelines (4 studies, 446 women; risk ratio 0.66; 95% CI 0.53-0.83) and reduced the incidence of hypertension (2 studies; 243 women; risk ratio 0.34; 95% CI 0.13-0.91).…”
Section: Recommendations On Nutrition During Preconceptionmentioning
confidence: 99%
“…Longerterm followups will be required to determine whether children receiving metformin treatment in utero develop less visceral fat and, potentially, increased insulin sensitivity. Previous evidence suggests that dietbased interventions are effective in achieving a reduction in gestational weight gain in pregnant women with GDM who are overweight or obese, but result in no substantial effect on birth weight, as reviewed elsewhere 216,217 . However, a promising approach in women with GDM is the use of a diet higher in complex carbohydrates and lower in fats; a study in pregnant women with GDM showed improved maternal and infant outcomes after only 7 weeks of treatment 218,219 .…”
Section: Targeting the Gut–liver Axismentioning
confidence: 99%
“…Other stakeholders have been specifically addressed with targeted communication. Evidence-based recommendations on optimized practice of nutrition before and during pregnancy, during the breast feeding period and the early life of infants, have been developed based on the project results and on systematic reviews of available evidence [35,36,37,38,39,40,41,42], in close collaboration with a broad group of stakeholders (prepared for publication). These recommendations are of considerable importance because most of the current guidance for pregnant women, particularly obese women, and for young children does not take into account the long-term programming consequences of early nutrition.…”
Section: Further Disseminationmentioning
confidence: 99%